لترقية سيطرة الطالبات على صيغ الفعل بمعهد المدينة الدينية شمس الضحى أتشيه الشمالية Chart Table فعالية استخدام - Ulfi Hayati (UIN Fatmawati Sukarno Bengkulu, 2022)
The educational medium plays a significant role in teaching and learning activities in transferring materials to students. The Chart Table helped the teacher to teach grammar about Arabic verb forms. If the teacher asks the students only to memorize the verb conjugation, he will find it difficult to distinguish the pronouns for each verb. Therefore, the objectives of this thesis are to identify the use of Chart Table in verb forms and to identify the effectiveness of Chart Table in promoting students' control over it according to pronouns. The research method used is quasi-experimental with a time series design, with its tools, interview, observation, post-test, and data analysis by T-test. You get that the students’ ability in verb forms is high, as the use of the Chart Table affects the students’ control in morphology education and is effective in promoting students’ control in Arabic verb forms in the Institute of Shams Al-Duha, North Aceh.